Rethinking village malaria workers in Cambodia: Perspectives from the communities, programme managers, and international stakeholders. - Long Heng Orng; Monnaphat Jongdeepaisal; Panarasri Khonputsa; Lek Dysoley; Siv Sovannaroth; Thomas J Peto; James J Callery; Christopher Pell; Richard J Maude; Marco Liverani (PLOS Global Public Health)
Since the early 2000s, malaria cases in Cambodia have declined steadily. Village malaria workers (VMWs) have played a critical role in reducing malaria transmission and progress towards malaria elimination. To prevent malaria re-establishment, however, implementation strategies need to consider carefully the changing healthcare needs in the communities as well as challenges to, and opportunities for, programme adaptation. We conducted in-depth interviews with a diverse range of stakeholders involved in the planning or implementation of the VMW programme in Cambodia, to elicit their views and experiences about health priorities in the communities, the public health value of VMWs and community-based care, and prospects for future programme development. Respondents included managers and implementers involved in the VMW programme at the central and provincial level (n = 9), technical officers at international agencies in Cambodia (n = 7), international stakeholders in non-governmental and research organisations based in Cambodia or other countries in the region (n = 5), as well as VMWs (n = 10), and community members (n = 16) in six endemic communes of Kravanh District, Pursat Province. In Kravanh, we also conducted four focus group discussions with 19 community members who had previous experience of malaria. The qualitative dataset was analysed using a thematic approach. VMWs, particularly mobile malaria workers tasked with active case detection among forest workers, were deemed necessary to maintain effective malaria control. However, there was a clear demand in the communities for additional services including treatment for common illnesses, monitoring of blood pressure and blood sugar levels, and relief of general symptoms through medication, such as for fever, headache, and stomach pain. Programme managers and international stakeholders agreed that the VMW programme needs a rethinking of the current implementation model to ensure continued uptake, relevance, and motivation of VMWs. Suggestions for add-on activities included adoption of new tests for febrile illnesses such as dengue and chikungunya, and screening for the prevention and monitoring of non-communicable diseases. There was emphasis on the needs for more sustainable financing mechanisms and integration with the existing community health infrastructure. The potential expansion of VMW services will benefit from the continued involvement of external donors and partners for technical and financial support. However, the implementation strategy should consider since the outset opportunities for enhanced local ownership and health system integration. To maintain domestic political momentum and access new potential sources of domestic funding, further programme development should align with national health priorities and the ongoing process of administrative decentralisation, while being responsive to changing public health needs within the communities.